Development of Nitrogen-Doped Carbon Catalysts Using Melamine-Based Polymer as a Nitrogen Precursor for the Oxygen Reduction Reaction. Issue 7 (11th April 2015) - Lee, Woong Hee; Lee, Dong Wook; Kim, Hansung
Abstract : Nitrogen-doped carbon catalysts for the oxygen reduction reaction (ORR) were synthesized using the pyrolysis of melamine-based polymer coated carbon black in the presence of cobalt. The linear sweep voltammogram that was recorded in an alkaline solution shows that the ORR activity of the nitrogen-doped carbon catalysts increases significantly close to that of Pt/C when a polymerized melamine is used as a nitrogen precursor instead of a melamine monomer. From the XPS-N 1s analysis, the introduction of the melamine-based polymer positively contributes to the nitrogen doping content and formation of a graphitic-N and pyridinic-N, which is known to be an active site for the ORR. Therefore, based on the quantitative analysis of the experimental results, melamine-based polymer is a promising precursor of nitrogen-doped carbon catalysts for ORR catalysts.